Derivación de valores económicos de la producción de leche de bovinos en la parroquia Isinlivi, utilizando funciones de beneficio. - Quindil Ayala, María Margarita (2023)
The research was carried out in the Isinliví parish, Sigchos Canton of the Cotopaxi province, for the time of 4 months of the year 2022 with the purpose of economic valuation in the production of bovine milk in the sector. The exploratory, descriptive methodology was used through visits, socialization, application of registration and surveys to the inhabitants of the sector who accepted to be part of the project, who provided relevant information about their animals and allowed to take data on the production system expenses and other data of interest for research such as weight, milk density and presence of mastitis. Through the data obtained it was determined that: the production system used in the parish is traditional, extensive, in the properties that accepted to be part of the project 206 animals were registered, of which 63% are dairy cows being 72.8% animals typical of the sector where the mixed race breed predominates with 82.5%, with an average age of 40.03 months, the evaluation of daily weight gain shows that infants lead with 19%, the average lactation days are 194, in which cows produce on average 6.99 kg of milk per day with a milk density of 1 .301 Kg/L on average, positive mastitis was also obtained with 0.8% of the total evaluated through the application of mastitis California Test, in the registered territory there are 1 .2 animals/ha, where production costs are high $ 0.65 compared to $0.42, which is the price of a liter of milk, this difference clearly does not allow profitability to be achieved. The parish has many resources to become a relevant sector in dairy production, however, it needs support to improve the management of pastures, animals and resource management in general.